2018
DOI: 10.1016/j.athoracsur.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram Predicting Recurrence and Guiding Adjuvant Radiation for Thymic Carcinoma After Resection

Abstract: Our nomogram for predicting recurrence-free survival had good performance. Adjuvant radiotherapy should be recommended for patients with a total score greater than 208.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…For example, preoperative nomograms estimating the risk of positive surgical margins and LNM could help clinicians identify patients who might benefit more from more extensive surgery (13,18). Postoperative nomograms estimating recurrence, cancer-specific survival, benefit of adjuvant therapies and the effect of treatment on quality of life might assist patients and physicians in making decision in all aspects (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…For example, preoperative nomograms estimating the risk of positive surgical margins and LNM could help clinicians identify patients who might benefit more from more extensive surgery (13,18). Postoperative nomograms estimating recurrence, cancer-specific survival, benefit of adjuvant therapies and the effect of treatment on quality of life might assist patients and physicians in making decision in all aspects (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Since thymic neuroendocrine tumors differ significantly in the survival of individual patients, the Masaoka-Koga (MK) staging system or the TNM staging system cannot be accurately used to predict survival. [7][8][9] Although some prognostic models have been studied, 4,10 nomogram models for thymic neuroendocrine tumors have not been developed. Therefore, in our study, we attempted to develop a nomogram model to predict and validate long-term survival rates for individualized treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The patient populations in each study varied, and taken together, there is no clear consensus on the benefit of PORT. Similarly, several single institutional trials have demonstrated a benefit to PORT in sub-populations of thymoma patients [Table 5] [31][32][33][34][35] .…”
Section: Post-operative Radiation Therapymentioning
confidence: 99%